The negative impact of free-fire online game addiction in elementary schools - Anwar Yoedo Pratama; Zaka Hadikusuma Ramadan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The attitude of addiction or addiction to online games is one attitude that will hurt its users. The negative impact of playing online games can be seen in several aspects, such as health, psychological, academic, social, and financial aspects. This study aims to describe the negative impacts of the excessive use of free-fire online games and the teachers' efforts to overcome this addictive attitude. This research uses a case study approach and a type of qualitative research. A case study is research used to explore a particular phenomenon (case) at one time and collect in-depth information with various procedures. Data collection methods are observation, interviews, and documentation. The data validity in this study uses the triangulation technique, and the data analysis used is the Miles and Huberman interactive model. The results of the study show that, in reality, on the ground, playing free-fire online games without excessive control will cause several negative impacts, including: causing addiction, speaking rudely and dirty, neglecting real-world activities, and inability to socialize. Meanwhile, the efforts made by teachers to overcome addiction to online free-fire games are to provide advice and build exemplary communication with parents.